Case of Sudden Death Cause of Tubal Pregnancy Rupture - Atılmış, Ümit Ünüvar; Şam, Bülent; Akyıldız, Elif Ülker; Öztürk, Osman; Ekizoğlu, Oğuzhan (The Bulletin of Legal Medicine, 2007)
Ectopic pregnancy is the leading cause of pregnancy-related death during the first trimester. Tubal ovum implantation is called tubal pregnancy. Tubal pregnancy may cause sudden death because of rupture and bleeding into abdominal cavity. These kinds of sudden death are rare. Difficulties in diagnosis are frequent. Especially, ectopic pregnancy must be suggested at sudden death of young women. 22-years-old woman with abdominal pain, who went under a curettage 3-4 weeks ago, died on the way to the hospital. In autopsy, there was 2500 cc hemorrhage in abdominal cavity, uterin cavity was empty, great hemotama with rupture area in right tubal cavity was found. At the histopathologic examination of tubal mass specimens, chrorionic villi were seen in the coagulum and tubal pregnancy was determined. Clinic and autopsy findings were evaluated together and the importance of ectopic pregnancy on forensic medicine was discussed. Key words: Ectopic pregnancy, tubal rupture, bleeding, sudden death, autopsy.